2020
DOI: 10.3389/fmicb.2020.00422
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Context for the Evolution and Transmission of Community-Associated Staphylococcus aureus ST59 Through the Food Chain

Abstract: Sequence type 59 (ST59) is a predominant clonal lineage of community-acquired, methicillin-resistant Staphylococcus aureus (CA-MRSA) in Asia. Despite its increasing clinical relevance in China, the evolution and geographic expansion of ST59 has been relatively uncared for. Previous study has shown that ST59 was the predominant clone in food-related MRSA in China. This study compared the genomes of 87 clonal complex (CC) 59 S. aureus isolates sourced from food chain and infection cases to reconstruct the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 65 publications
(77 reference statements)
5
27
1
Order By: Relevance
“…Previous studies have suggested that ST59 evolved concurrently in both North America (NA), previously referred to as the United States lineage and East Asia (EA), with strains from each region belonging to separate and distinct sub-lineages ( Ward et al, 2016 ), with mobile genetic elements playing a part ( Hung et al, 2016 ). For a more detailed look into the evolution of the ST59 lineage, a Bayesian inference phylogenomic tree, comprised of both the monomorphic SNPs and insertions/deletions identified by snippy, was generated incorporating our isolates (red font), as well as select isolates from the Ward et al (2016) (blue font) and Pang et al (2020) (green font) studies, and ST59 sequences downloaded from NCBI (black font). Molecular typing data was determined for the downloaded sequences, with IEC type identified for all isolates, and MES type for a random selection of isolates.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have suggested that ST59 evolved concurrently in both North America (NA), previously referred to as the United States lineage and East Asia (EA), with strains from each region belonging to separate and distinct sub-lineages ( Ward et al, 2016 ), with mobile genetic elements playing a part ( Hung et al, 2016 ). For a more detailed look into the evolution of the ST59 lineage, a Bayesian inference phylogenomic tree, comprised of both the monomorphic SNPs and insertions/deletions identified by snippy, was generated incorporating our isolates (red font), as well as select isolates from the Ward et al (2016) (blue font) and Pang et al (2020) (green font) studies, and ST59 sequences downloaded from NCBI (black font). Molecular typing data was determined for the downloaded sequences, with IEC type identified for all isolates, and MES type for a random selection of isolates.…”
Section: Resultsmentioning
confidence: 99%
“… Maximum clade credibility tree showing the phylogenetic relationship between our ST59 isolates, along with global isolates from studies by Ward et al (2016) and Pang et al (2020) . Branch colors represent the 6 sub-lineages, with WGS-1 represented by gray, WGS-2 by purple, WGS-3 by orange, WGS-4 by pink, WGS-5 by blue and WGS-6 by green.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations